Order short-term memory is not impaired in dyslexia and does not affect orthographic learning - Staels, Eva; Van den Broeck, Wim (Frontiers in Human Neuroscience, 2014)
This article reports two studies that investigate short-term memory (STM) deficits in dyslexic children and explores the relationship between short-term memory and reading acquisition. In the first experiment, thirty-six dyslexic children and sixty-one control children performed an item STM task and a serial order STM task. The results of this experiment show that dyslexic children do not suffer from a specific serial order STM deficit. In addition, the results demonstrate that phonological processing skills are as closely related to both item STM and serial order STM. However, nonverbal intelligence was more strongly involved in serial order STM than in item STM. In the second experiment, the same two STM tasks were administered and reading acquisition was assessed by measuring orthographic learning in a group of one hundred and eighty-eight children. The results of this study show that orthographic learning is exclusively related to item STM and not to order STM. It is concluded that serial order STM is not the right place to look for a causal explanation of reading disability, nor for differences in word reading acquisition.